2009
DOI: 10.2114/jpa2.28.63
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Exertion is Not Necessarily Associated with Altered Brain Activity during Exercise

Abstract: Previous studies have investigated the relationship between prefrontal cortex activation and perceived exertion during prolonged exercise. However, the effect of perceived exertion on prefrontal cortex activity is confounded by exercise intensity. Therefore, the changes in prefrontal cortex activity in response to perceived exertion remain unclear. The purpose of the present study was to investigate the relationship between the activation (oxygenation) of the prefrontal cortex and perceived exertion during con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…RPE increased progressively throughout the time trial, whereas Cox fluctuated), which is surprising if it is believed that cerebral deoxygenation is causally associated with perception of effort. First indices of such a relationship may be found in the recent work of Shibuya et al (2009) which revealed that perceived exertion during a submaximal contraction of the elbow flexors is not necessarily associated with prefrontal cortex oxygenation. These results indicate that the selection of the pace at the beginning of an exercise may not be associated with prefrontal cortex activity per se, but rather with other sensory signals (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…RPE increased progressively throughout the time trial, whereas Cox fluctuated), which is surprising if it is believed that cerebral deoxygenation is causally associated with perception of effort. First indices of such a relationship may be found in the recent work of Shibuya et al (2009) which revealed that perceived exertion during a submaximal contraction of the elbow flexors is not necessarily associated with prefrontal cortex oxygenation. These results indicate that the selection of the pace at the beginning of an exercise may not be associated with prefrontal cortex activity per se, but rather with other sensory signals (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Shibuya et al [20 ]measured prefrontal cortex oxygenation levels of healthy subjects during elbow flexion CWRE with or without muscle spindle stimulation, which can decrease perceived exertion. Cerebral oxygenation increased with exercise, but oxy-Hb concentration was not changed by muscle spindle stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Mild cycling CWRE with NIRS recording was performed at a working intensity corresponding to 40% of a subject’s symptom-limited peak work rate achieved during the incremental exercise test at visit 3. To avoid the interfusion of the effects of exercise intensity and perceived exertion on prefrontal activation, the exercise intensity was set to a stable level (constant work rate) [20]. Ide et al [21] reported that arterial lactate accumulation did not change significantly during mild exercise (30% of maximum oxygen consumption, V O 2 max), but it increased during maximal exercise (60% of V O 2 max).…”
Section: Methodsmentioning
confidence: 99%
“…During an incremental exercise test, 8 min of low-intensity CWRE was undertaken after a 1-min rest and 1-min warm-up period, with NIRS being recorded at a work intensity corresponding to 40% of a participant's symptom-limited peak work rate [21]. PDI was determined each minute, during both exercise and rest periods, using the 10-point Borg scale [22,23].…”
Section: Multichannel Nirsmentioning
confidence: 99%